Study of membrane restrictors in hydrostatic bearing - Dyi-Cheng Chen (Advances in Mechanical Engineering, 2018)
Hydrostatic guides or bearings are very important crucial components in precision mechanical system. First, the article selects the structural parameters of the standard design film restrictor with regard to hydrostatic bearing. Moreover, using COMSOL, the article performs the fluid–structure interaction analysis of the diaphragm to obtain pressure and stress field distribution, and the deformation of diaphragm in membrane restrictors. Then, fluid resistance and other related properties of the membrane restrictors are obtained, and the related parameters including oil pressure, restrictor gap, membrane thickness, and membrane restrictors to perform feedback action of different oils are explored. Finally, the simulation results and experimental measurements are compared to verify their feasibility. In this study, an oil pressure of 10 bar induced deformation of the membrane with consistent trend; however, oil pressures of 30 and 50 bar induced large error with the same trend.